2017
DOI: 10.1108/qaoa-10-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

A discrete choice experiment to explore carer preferences

Abstract: This paper describes a case study to test the applicability of the Discrete Choice Experiment (DCE) method to assess the preferences of carers of people with dementia. The focus of enquiry was home care provision. Design/methodology/approach A multi-method approach was adopted for this pilot study. A literature review identified key characteristics of home care for dementia. This informed consultations with lay representatives. Key attributes of home care for the DCE were identified and formed the basis for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 29 publications
(46 reference statements)
0
31
1
Order By: Relevance
“…At an interpersonal level, it is known that communication with care workers has the potential to either reinforce or compromise an older person's identity and selfhood, especially in the context of cognitive decline, depending on how it is delivered . Indeed, for patients with dementia and their carers, preference studies have indicated that continuity of care is prioritised above other features, supporting the argument that relational aspects of care are crucial to wellbeing in this population.…”
Section: Introductionmentioning
confidence: 99%
“…At an interpersonal level, it is known that communication with care workers has the potential to either reinforce or compromise an older person's identity and selfhood, especially in the context of cognitive decline, depending on how it is delivered . Indeed, for patients with dementia and their carers, preference studies have indicated that continuity of care is prioritised above other features, supporting the argument that relational aspects of care are crucial to wellbeing in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The oldest included study was published in 2010 (Nieboer et al 2010) and seven of the ten studies were published in 2017 or afterwards (Chester et al 2017;Chester et al 2018;Fahey et al 2017;Jasper et al 2018;Kampanellou et al 2019;Teahan et al 2021;Walsh et al 2020). Four studies were conducted in the United Kingdom (Chester et al 2017;Chester et al 2018;Jasper et al 2018;Kampanellou et al 2019), three in Ireland (Fahey et al 2017;Teahan et al 2021;Walsh et al 2020), two in the Netherlands (Groenewoud et al 2015;Nieboer et al 2010), and one in Japan (Sawamura et al 2015). It should be noted that the publications from the United Kingdom, Ireland, and the Netherlands were conducted by the same institutions and/or partially by the same individuals.…”
Section: Year Of Publication and Country Of Originmentioning
confidence: 99%
“…In nine of the ten included studies, a DCE experiment was conducted (Chester et al 2017;Chester et al 2018;Groenewoud et al 2015;Jasper et al 2018;Kampanellou et al 2019;Nieboer et al 2010;Sawamura et al 2015;Teahan et al 2021;Walsh et al 2020), and in one study, the method of CA was applied (Fahey et al 2017).…”
Section: Types Of Mcdamentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the preferences of people with dementia and cognitive impairment, DCEs have traditionally been conducted with proxies (e.g. carers) rather than consumers themselves (Arora et al., 2019; Chester et al., 2017; Ratcliffe et al., 2019). More recently, DCEs have been successfully applied in aged care settings including older people with mild cognitive impairment and mild dementia (Kaambwa et al., 2015; Milte et al., 2019).…”
Section: Introductionmentioning
confidence: 99%